Longitudinal Magnetic Resonance Spectroscopy and Diffusion Tensor Imaging in Sheep (Ovis aries) With Quinolinic Acid Lesions of the Striatum: Time-Dependent Recovery of N-Acetylaspartate and Fractional Anisotropy. Issue 10 (2nd August 2020) - O'Connell, Adam B; Kuchel, Timothy R; Perumal, Sunthara R; Sherwood, Victoria; Neumann, Daniel; Finnie, John W; Hemsley, Kim M; Morton, A Jennifer
Abstract: We created an excitotoxic striatal lesion model of Huntington disease (HD) in sheep, using the N -methyl-d -aspartate receptor agonist, quinolinic acid (QA). Sixteen sheep received a bolus infusion of QA (75 µL, 180 mM) or saline, first into the left and then (4 weeks later) into the right striatum. Magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI) of the striata were performed. Metabolite concentrations and fractional anisotropy (FA) were measured at baseline, acutely (1 week after each surgery) and chronically (5 weeks or greater after the surgeries). There was a significant decrease in the neuronal marker N -acetylaspartate (NAA) and in FA in acutely lesioned striata of the QA-lesioned sheep, followed by a recovery of NAA and FA in the chronically lesioned striata. NAA level changes indicate acute death and/or impairment of neurons immediately after surgery, with recovery of reversibly impaired neurons over time. The change in FA values of the QA-lesioned striata is consistent with acute structural disruption, followed by re-organization and glial cell infiltration with time. Our study demonstrates that MRS and DTI changes in QA-sheep are consistent with HD-like pathology shown in other model species and that the MR investigations can be performed in sheep using a clinically relevant human 3T MRI scanner.